(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Based on Jean-Luc-Nancy’s critical reflections on the inoperability of the concept of community following the failure of the ontological conception of the common (the nature of being in community), this essay seeks to position the collective creation practices of Brazilian group theatre as a possible methodological response for the formation of non-ontological communities, sustained through the act of becoming-common as an ethical-artistic practice – the community-group.